2018
DOI: 10.1038/s41598-018-20235-1
|View full text |Cite
|
Sign up to set email alerts
|

Plant probiotic bacteria Bacillus and Paraburkholderia improve growth, yield and content of antioxidants in strawberry fruit

Abstract: Strawberry is an excellent source of natural antioxidants with high capacity of scavenging free radicals. This study evaluated the effects of two plant probiotic bacteria, Bacillus amylolequefaciens BChi1 and Paraburkholderia fungorum BRRh-4 on growth, fruit yield and antioxidant contents in strawberry fruits. Root dipping of seedlings (plug plants) followed by spray applications of both probiotic bacteria in the field on foliage significantly increased fruit yield (up to 48%) over non-treated control. Enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
143
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(155 citation statements)
references
References 43 publications
10
143
2
Order By: Relevance
“…In the opinion of those authors, the largest increase in fruit weight was obtained following the use of bacteria and fungi (Bacillus velezensis and Rhizophagus intraradices) at the beginning of the strawberry growing cycle. According to Rahman et al (2018), it is very effective to use bacterial preparations by treating the root system and by foliar application. The cited authors claim that these ways of applying Bacillus amyloliquefaciens BChi1 and Paraburkholderia fungorum BRRh-4 in the case of the strawberry cultivar "Festival" can increase yields by up to 43% and 48%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In the opinion of those authors, the largest increase in fruit weight was obtained following the use of bacteria and fungi (Bacillus velezensis and Rhizophagus intraradices) at the beginning of the strawberry growing cycle. According to Rahman et al (2018), it is very effective to use bacterial preparations by treating the root system and by foliar application. The cited authors claim that these ways of applying Bacillus amyloliquefaciens BChi1 and Paraburkholderia fungorum BRRh-4 in the case of the strawberry cultivar "Festival" can increase yields by up to 43% and 48%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Production of IAA by Streptomyces spp. (Abd‐Alla et al , ) and members of the Bacillus genus (Rahman et al , ) have previously been reported. However, the Streptomyces isolate 136 could not produce IAA and also did not exhibit any ability to solubilize inorganic phosphorus in vitro .…”
Section: Discussionmentioning
confidence: 95%
“…Production of IAA by Streptomyces spp. (Abd-Alla et al, 2013) and members of the Bacillus genus (Rahman et al, 2018) have previously been reported. However, the Streptomyces isolate 136 could not produce IAA and also did not exhibit any ability to solubilize inorganic phosphorus Figure 4 Effect of white rot (Sclerotium cepivorum; Sc) and pretreatment with endophytic bacteria on expression of alliin lyase 2 and accumulation of alliin in the stems of garlic seedlings.…”
Section: Groupmentioning
confidence: 91%
“…According to most studies on strawberries, the PGPMs showed a positive effect on their growth and development [45]- [50].…”
Section: Discussionmentioning
confidence: 99%